Analysis of Campus Model School Development Strategies in Improving the Quality of SD Negeri Petungan Campus, South Cilacap District - Nati Nati; Yahya Sudarya (UM Purwokerto Press, 2023)
School strategies are important policies from schools to achieve the goal of improving and developing school quality. (Fatikah Noor, 2019). The right strategy can have an impact on the success of the school in achieving its goals. To get the right strategy, schools need to know information about the factors in schools that can support success in achieving goals. Schools need to analyze these factors. The implementation of this analysis is expected to provide information that can be used as a reference in developing strategies so as to obtain good quality education. The aims of the study were (1) to describe the strategic planning for the campus model school development at SD Negeri Kampus Petungan, South Cilacap District; (2) explaining the coordination of the campus model school development strategy at SD Negeri Petungan Campus, South Cilacap District; (3) describes the supervision of the campus model school development strategy in SD Negeri Petungan Campus, South Cilacap District. This research took place at SD Negeri Petungan Campus, South Cilacap District. The research used was field research with a descriptive qualitative approach using a case study model. Qualitative research according to sharpness and accuracy in observing, noting a process and activity that appears in reality. And analyze it in a meaningful unit. The research subjects used in this study were school heads, teachers and education staff at the SDN Petungan Cilacap Selatan Campus. Research result: Campus system model schools are schools that are located close to each other. In fact, the schools are still one door by implementing a semi-independent or joint management system. In the sense that all management activities are carried out jointly, but there are some things that must be carried out independently by the school. The coordination carried out is vertical and horizontal coordination. There is one school principal who is the coordinator who manages several other school principals. Oversight of the roles of personnel who already have duties, authorities and carry out their implementation needs to be carried out so that they are in accordance with the goals, vision and mission of the company/organization.